Seaweed as novel food for prevention and therapy for life style related disease - Lindarsih Notowidjojo (World Nutrition Journal, 2021)
Seaweed has long been known and consumed as a functional food and folk medicine, especially in people who live in coastal areas. Research on seaweed has recently increased with the surge need for alternative sources of functional food to deal with health problems related to lifestyle, such as obesity, diabetes, hypertension and cardiovascular disease. Epidemiology studies have found that population consumed seaweed is on a regular basis have significantly less diet-related diseases.1,2 Even the largest population of old age is in Japan, which consumes the most seaweed in the world.1,3 In countries such as Japan, China, and Korea, approximately 66% of algae species have been used as a daily ingredient in their dishes for many years.